Strategi Diet untuk Mengurangi Inflamasi dan Penyakit Metabolisme: Sebuah Tinjauan Pustaka Naratif - Budhi Setiawan; ernawati (Calvaria Medical Journal, 2023)
Introduction: Inflammation plays a pivotal role in the pathogenesis of various health conditions, ranging from chronic diseases to autoimmune disorders. This narrative review delves into the intricate relationship between nutrition and inflammation, exploring the potential of dietary interventions as an alternative in mitigating metabolic conditions. Method: The relevant articles from databases such as PubMed, Scopus, Web of Science, and Google Scholar in the recent years have been extracted using the main keywords were: metabolic, omega 3, inflammation, gut microbiota, dietary pattern, polyphenols, dietary fiber, probiotics, and anti-inflammatory diet. Result: This review discussed the molecular mechanisms underlying inflammation and how certain dietary components can either exacerbate or mitigate these processes. The role of dietary patterns, such as the mediterranean, dietary approach to stop hypertension (DASH), plant-based diet, and anti-inflammatory diets, in promoting overall health and reducing inflammation. These patterns emphasize the consumption of whole foods rich in anti-inflammatory agents while minimizing pro-inflammatory substances. The complex interaction between the gut microbiota and dietary factors, underscoring the bidirectional relationship that influences inflammatory outcomes. Conclusion: the multifaceted exploration presented herein underscores the potential of nutrition as a modifiable factor in promoting anti-inflammatory environments within the body.